Juridical Review of Early Marriage in Tangerang District Based on Islamic Family Law in Indonesia - Dofana Givanti; Benny Djaja (PT Publikasiku Academic Solution, 2023)
Indonesia sets the age for marriage regulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, in this regulation, there is a change in the age of marriage for women, namely from 16 years to 19 years. Article 15 paragraph (1) of the Compilation of Islamic Law (KHI) also regulates the age of marriage, namely 19 years for men and 16 years for women. The limitation on the age of marriage aims to make the prospective bride and groom more ready to live in the household. In Indonesia, the practice of early marriage is still rife, therefore researchers are interested in studying early marriage in Tangerang District. In this study, there are two main issues, namely: How to regulate early marriage according to Islamic family law in Indonesia and what factors are causing early marriage in Tangerang Regency. This study uses normative legal research methods supported by empirical data, using secondary data which is then analyzed qualitatively. The results of the study describe the regulation of early marriage according to Islamic family law in Indonesia that in matters related to early marriage, it is not permissible to ignore the Compilation of Islamic Law (KHI) and the Marriage Law No. 1 of 1974, even though on the grounds that early marriage in a legal view Islam is not prohibited directly or textually. Because it is the main source in the implementation of marriage law, especially in Islamic family law in Indonesia. And the factors that cause early marriage in Tangerang Regency are parents' will, promiscuity, custom and culture, economics, religion, and education. However, the dominating factors are promiscuity factors and economic factors